Cadmium binding during leaf senescence in Festuca arundinacea: Promotion phytoextraction efficiency by harvesting dead leaves. (February 2022) - Zhang, Jiaxin; Fei, Ling; Dong, Qin; Zuo, Shaofan; Li, Yanbang; Wang, Zhaolong
Abstract: Phytoextraction by harvesting dead leaves is a novel cadmium (Cd) phytoremediation strategy in tall fescue ( Festuca arundinacea ), which provides feasibility for the phytoremediation of Cd-polluted soils and cleaner food production. The highest Cd in dead leaves is the result of Cd accumulation during the process of leaf senescence. However, it is not known the mechanism of Cd accumulation during the leaf senescence, which limits the phytoextraction efficiency of this technology. In this study, we found that the contents of phytochelatins (PC), glutathione (GSH), and non-protein thiols (NPT) were increased during the process of leaf senescence and Cd stress significantly promoted PC, GSH, and NPT. Transcriptome analysis showed that the pathway of glutathione metabolism was significantly enriched in the senescent leaf under Cd stress. 19 genes encoding GST, enzymes catalyzing GSH-Cd binding, were up-regulated in the senescent leaf. The increases of PC, GSH, and NPT in the senescent leaf for Cd-binding could be from the pathways of the protein degradation rather than their synthesis, because genes encoding cysteine protease (catalyzes protein degradation) were significantly promoted, but both GSH synthetase (GS) and PC synthetase (PCS) did not show the significant changes between the young and senescent leaves. Our results indicated that Cd accumulation during the leaf senescence could be the result of the promotion of Cd-binding by PC, GSH, and NPT, which provide insights into the regulatory mechanism and further genetic engineering to promote the phytoextraction efficiency by harvesting dead leaves in tall fescue. Graphical abstract: Image 1 Highlights: Cd-binding of PCs, GSH, and NPTs contributed to Cd accumulation during leaf senescence. 17 GST genes were up-regulated during leaf senescence. MT-Cd binding was not responsible for the Cd accumulation in the senescent leaf. PCs, GSH, NPTs in the senescent leaf could be from the protein degradation. Cd-binding is a way to promote phytoextraction efficiency by harvesting dead leaves.